PENGARUH ENVIRONMENTAL PERFORMANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sari, Eka Lala; Widyastuti, Tri; Maidani, Maidani; Sari, Pratiwi Nila (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to examine the influence of Environmental Performance and Corporate Social Responsibility on Financial Performance. The population in this research is all Energy companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sampling technique used is purposive sampling method with predetermined criteria, so that a sample of 80 data from 20 companies for 4 years is obtained. The type of data used is secondary data obtained from the company’s annual report for the 2019-2022 period. Hypothesis testing in this research used multiple linear regression analysis methods using the SPSS 26.0 program. The results of this research indicate that partially the Environmental Performance variable has a positive effect on Financial Performance, while the Corporate Social Responsibility variable has no effect on Financial Performance and simultaneously the Environmental Performance and Corporate Social Responsibility variables have a positive effect on Financial Performance.